The Effect of Overdose Education and Naloxone Distribution: An Umbrella Review of Systematic Reviews - Razaghizad, Amir; Windle, Sarah B.; Filion, Kristian B.; Gore, Genevieve; Kudrina, Irina; Paraskevopoulos, Elena; Kimmelman, Jonathan; Martel, Marc O.; Eisenberg, Mark J. (American journal of public health (1971), 2021)
Background. Opioids contribute to more than 60 000 deaths annually in North America. While the expansion of overdose education and naloxone distribution (OEND) programs has been recommended in response to the opioid crisis, their effectiveness remains unclear. Objectives. To conduct an umbrella review of systematic reviews to provide a broad-based conceptual scheme of the effect and feasibility of OEND and to identify areas for possible optimization. Search Methods. We conducted the umbrella review of systematic reviews by searching PubMed, Embase, PsycINFO, Epistemonikos, the Cochrane Database of Systematic Reviews, and the reference lists of relevant articles. Briefly, an academic librarian used a 2-concept search, which included opioid subject headings and relevant keywords with a modified PubMed systematic review filter. Selection Criteria. Eligible systematic reviews described comprehensive search strategies and inclusion and exclusion criteria, evaluated the quality or risk of bias of included studies, were published in English or French, and reported data relevant to either the safety or effectiveness of OEND programs, or optimal strategies for the management of opioid overdose with naloxone in out-of-hospital settings. Data Collection and Analysis. Two reviewers independently extracted study characteristics and the quality of included reviews was assessed in duplicate with AMSTAR-2, a critical appraisal tool for systematic reviews. Review quality was rated critically low, low, moderate, or high based on 7 domains: protocol registration, literature search adequacy, exclusion criteria, risk of bias assessment, meta-analytical methods, result interpretation, and presence of publication bias. Summary tables were constructed, and confidence ratings were provided for each outcome by using a previously modified version of the Royal College of General Practitioners’ clinical guidelines. Main Results. Six systematic reviews containing 87 unique studies were included. We found that OEND programs produce long-term knowledge improvement regarding opioid overdose, improve participants’ attitudes toward naloxone, provide sufficient training for participants to safely and effectively manage overdoses, and effectively reduce opioid-related mortality. High-concentration intranasal naloxone (> 2 mg/mL) was as effective as intramuscular naloxone at the same dose, whereas lower-concentration intranasal naloxone was less effective. Evidence was limited for other naloxone formulations, as well as the need for hospital transport after overdose reversal. The preponderance of evidence pertained persons who use heroin. Author’s Conclusions. Evidence suggests that OEND programs are effective for reducing opioid-related mortality; however, additional high-quality research is required to optimize program delivery. Public Health Implications. Community-based OEND programs should be implemented widely in high-risk populations.